Idiopathic inflammatory myopathy associated with Sjögren’s disease: features of a distinct clinical entity - Konen, Franz Felix; Güzeloglu, Yunus Emre; Seeliger, Tabea; Jendretzky, Konstantin Fritz; Nay, Sandra; Grote-Levi, Lea; Schwenkenbecher, Philipp; Gründges, Christine; Ernst, Diana; Witte, Torsten; Skripuletz, Thomas (Frontiers in Immunology, 2025)
BackgroundIdiopathic inflammatory myopathies (IIM) and Sjögren’s disease (SjD) may coexist, but data on their combined presentation and treatment response remain limited.MethodsWe retrospectively analyzed 23 patients with biopsy-confirmed IIM and coexisting SjD, compared to 24 age- and sex-matched IIM controls without SjD. Clinical, electrophysiological, and immunological data, as well as treatments and outcomes, were assessed. Outcome assessment included EULAR Sjögren’s Syndrome Disease Activity Index (ESSDAI) and the ACR/EULAR Myositis Response Criteria for adult polymyositis and dermatomyositis.ResultsAmong IIM-SjD patients, 39% had inclusion body myositis (IBM), 61% had poly- or dermatomyositis. Compared to controls, asymmetric muscle weakness (78%, p=0.0012), non-muscular manifestations (52%, p=0.0035), and more immunosuppressive therapies (median 3; p=0.0253), including more frequent anti-CD20 use (30%, p=0.0039) were found in IIM-SjD. After a median follow-up of 80 months, patients showed better outcomes (lower ESSDAI and higher ACR/EULAR response scores; p=0.0031 and p=0.0083). IBM was a strong predictor of higher ESSDAI scores at follow-up (p=0.014).ConclusionsThe study suggests that IIM-SjD is characterized by more asymmetric muscle weakness and extramuscular involvement. Enhanced immunosuppression led to better outcomes in patients with poly- or dermatomyositis, while IBM was linked to higher disease activity. Further research is needed to clarify underlying mechanisms.